3-Monothiopomalidomide, a new immunomodulatory imide drug (IMiD), blunts inflammation and mitigates ischemic stroke in the rat - Kai-Yun Chen; Shih-Chang Hsueh; Pathik Parekh; Buyandelger Batsaikhan; David Tweedie; Weiming Luo; Chirag Patel; Yung-Hsiao Chiang; Nicholas Bambakidis; Barry J. Hoffer; Chi-Zong Huang; Seong-Jin Yu; et al. (GeroScience, 2025)
An overactive neuroinflammatory response is often evident in the elderly and is a significant contributor to brain tissue damage following acute ischemic stroke. Such an inflammatory response is largely mediated by microglial cells and peripheral blood mononuclear cells (PBMCs). Classical anti-inflammatory agents have not proved clinically effective in mitigating the impact of ischemic stroke but have highlighted targets for new drug development, in particular excessive proinflammatory cytokine release. The immunomodulatory imide drug (IMiD) class has shown potential in reducing neuroinflammation and switching microglial phenotypic expression away from a proinflammatory to a regenerative anti-inflammatory one. 3-Monothiopomalidomide (3-MP), a new IMiD, has a brain/plasma concentration ratio of 0.5 to 0.6, an oral bioavailability of 38.5%, and a monophasic disappearance of half-life 3.2 h following oral administration. 3-MP pretreatment mitigates lipopolysaccharide (LPS)-induced inflammation in cellular human PBMCs and, in rat studies, 3-MP pretreatment lowers proinflammatory cytokine levels in the conditioned media and in plasma and the brain, respectively. Administered systemically to rats challenged with middle cerebral artery occlusion (MCAo) and reperfusion, 3-MP post-MCAo treatment reduced infarction volume; improved body asymmetry, a behavioral measure of stroke impact; and lowered inflammation. In summary, 3-MP exerted neuroprotective effects via anti-inflammatory actions against MCAo-induced ischemic injury and represents a therapeutic that warrants further investigation as a treatment for brain damage and related disorders associated with excessive inflammation.

AMPK-dependent autophagy activation and alpha-Synuclein clearance: a putative mechanism behind alpha-mangostin’s neuroprotection in a rotenone-induced mouse model of Parkinson’s disease - Pathik Parekh; Nishant Sharma; Monika Sharma; Anagha Gadepalli; Adil Ali Sayyed; Sayan Chatterjee; Abhijeet Kate; Amit Khairnar (Metabolic Brain Disease, 2022)